SISTEM INFORMASI PELAYANAN HAJI BERBASIS WEB DI KELOMPOK BIMBINGAN IBADAH HAJI (KBIH) WADI FATIMAH - Khairunnisa, Ayu Nurul; Maksudi, Maksudi; Martinus, Agust Isa (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2024)
The Hajj pilgrimage is a form of worship that is mandatory for Muslims to carry out if they fulfill the requirements. This Hajj pilgrimage is regularly held every year and the number is increasing. KBIH activities are an effort to provide necessities for Hajj and Umrah pilgrims who will carry out and carry out the Hajj and Umrah pilgrimage, it will be difficult if they do not receive guidance and assistance during the Hajj and Umrah pilgrimage. This research is a Web-based Hajj Service Information System developed by the Wadi Fatimah Hajj Guidance Group (KBIH) to increase the efficiency of managing pilgrim data and conveying information. The development methodology uses the Waterfall model with analysis, design, implementation and testing stages. The results show an increase in service efficiency and effectiveness, facilitating access to information for the congregation and smooth administrative management for KBIH. With this system, it is hoped that it can improve the overall quality of service, improve information transparency, support better decision making, and maintain the security of congregation data. Keywords: Information Systems, Hajj, KBIH Wadi Fatimah